1973
DOI: 10.1002/art.1780160512
|View full text |Cite
|
Sign up to set email alerts
|

Renal histology and clinical course of systemic lupus erythematosus

Abstract: Thirty women with systemic lupus erythematosus were categorized into groups with and without significant renal involvement on the basis of renal biopsy and subsequently followed for an average of 9.4 years. At this time 53% of the patients with renal disease and 70% of the "nonrenal" patients had died. While 80% of the deaths in the "renal" group were due to renal disease, none of the nonrenal patients died of this complication. Major central nervous system involvement was eventually noted in 100% of the nonre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Group II contains those with Mes G or with normal findings. Mes G is a relatively mild focal lesion which has been shown to be associated with a good prognosis (16). 10 of the 11 patients with PGN and 3 of the 5 with Memb GN were LBT positive.…”
Section: Resultsmentioning
confidence: 99%
“…Group II contains those with Mes G or with normal findings. Mes G is a relatively mild focal lesion which has been shown to be associated with a good prognosis (16). 10 of the 11 patients with PGN and 3 of the 5 with Memb GN were LBT positive.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, cognitive impairment has not always been associated with excess morbidity (19)(20)(21). Although some studies have shown increased mortality in patients with NP disease (22)(23)(24)(25)(26), others have not (7,15,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…CNS involvement is more common in SLE patients without renal involvement (Petz et al, 1971;Cheatum et al, 1973). The present patient could have passed as such, since repeat kidney function tests and urine analyses and even the light microscopy study of her renal biopsy specimen were normal.…”
Section: Discussionmentioning
confidence: 64%